THE FACTORS RELATED TO OBESITY IN EAST JAKARTA CITY WORKERS - mannulang, Debora anastas agnesia (Perhimpunan Ahli Epidemiologi Indonesia, 2024)
Background: Obesity or commonly known as being overweight is a medical condition in which the body has excess fat which has accumulated negative effects on health. Obesity from a health perspective is a disease of malnutrition, as a result of consuming food that far exceeds one's needs. This study aims to determine the factors associated with the incidence of obesity in workers at PT X City of East Jakarta in 2023. Methods: This study used a quantitative approach with a cross-sectional study design. The population in this study were 75 workers and the sample used was 75 respondents with a total sampling technique. Results: The data will be analyzed using the chi-square test with the results showing that there is a significant relationship between age (p-value = 0.030), nutritional adequacy (p-value = 0.0005) and physical activity (p-value = 0.016). While the variable that has no significant relationship is gender (p-value = 0.896). Conclusion: Obesity was related to age, nutrition adequacy and physical activity.